2007
DOI: 10.1152/ajpcell.00176.2007
|View full text |Cite
|
Sign up to set email alerts
|

Localization of AMP kinase is regulated by stress, cell density, and signaling through the MEK→ERK1/2 pathway

Abstract: 5'-AMP-activated protein kinase (AMPK) serves as an energy sensor and is at the center of control for a large number of metabolic reactions, thereby playing a crucial role in Type 2 diabetes and other human diseases. AMPK is present in the nucleus and cytoplasm; however, the mechanisms that regulate the intracellular localization of AMPK are poorly understood. We have now identified several factors that control the distribution of AMPK. Environmental stress regulates the intracellular localization of AMPK, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
134
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 36 publications
9
134
1
1
Order By: Relevance
“…These findings expand earlier studies revealing that there is no direct link between the phosphorylation of Thr172 of AMPKα and the subcellular localization of total AMPKα. 32 Co-staining analyses of P-AMPKα Thr172 and α-tubulin in early and late stages of mitosis. At prophase, as chromosomes condense and the replicated centrosomes begin to separate, P-AMPKα Thr172 appeared to associate closely with the two asters of α-tubulin stained microtubules that begin to nucleate from mature centrosomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings expand earlier studies revealing that there is no direct link between the phosphorylation of Thr172 of AMPKα and the subcellular localization of total AMPKα. 32 Co-staining analyses of P-AMPKα Thr172 and α-tubulin in early and late stages of mitosis. At prophase, as chromosomes condense and the replicated centrosomes begin to separate, P-AMPKα Thr172 appeared to associate closely with the two asters of α-tubulin stained microtubules that begin to nucleate from mature centrosomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since NaN 3 is known to increase AMPK activity in other cell types (Jing and Ismail-Beigi, 2007;Guan et al, 2008;Kréneisz et al, 2009) we suggest that AMPK could be activated in the locust ventilatory neuropile in response to NaN 3 . AMPK activation can occur via different mechanisms (Hardie and Hawley, 2001;Lindsley and Rutter, 2004;Kodiha et al, 2007), and it is likely that AMPK was activated through different pathways in response to NaN 3 and AICAR. Given that AICAR induced rhythm changes without inducing SD, we conclude that AMPK is sufficient for the motor pattern changes induced by chemical anoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Our current model of AMPK trafficking proposes that the kinase shuttles between the nucleus and the cytoplasm. Data from our group and others support this idea, as they demonstrated that the nuclear carrier Crm1 is essential for AMPK export from the nucleus to the cytoplasm (Kazgan et al, 2010;Kodiha et al, 2007). How the subunit impacts the proper targeting of the holoenzyme is at present not entirely clear.…”
Section: Subcellular Distribution Of Ampk Substratesmentioning
confidence: 60%
“…The list of AMPK substrates was compiled from PhosphoSitePlus (phosphosite.org). AMPK is found in the nucleus and cytoplasm which reflects functions for the enzyme in both locations (Kodiha et al, 2007;Witczak et al, 2008). Although the kinase is associated with multiple compartments, 1 and 2 subunits differ in their nucleocytoplasmic distribution.…”
Section: Subcellular Distribution Of Ampk Substratesmentioning
confidence: 99%
See 1 more Smart Citation